254 AN AUDIT OF DISCHARGE SUMMARY QUALITY AND INTRODUCTION OF A DISCHARGE SUMMARY TEMPLATE IN AN ORTHOGERIATRIC SERVICE. (25th October 2022) - Rafferty, M; Murphy, D; Fouhy, F; Amumin, A; Saidova, M; Dukelow, T; Ahern, E
Abstract: Background: The discharge summary is the main method of communication integrating the care of older adults from the acute hospital admission to their discharge destination. HIQA published standards to ensure high quality and safe information transfer between settings. We designed an audit to evaluate the quality of the discharge summaries from the orthogeriatric service before and after the introduction of a discharge summary template for use by Non-Consultant Hospital Doctors (NCHDs) on the service Methods: Data were collected anonymously using an excel data collection tool with 51 data points covering the seven key areas outlined in the standards. Initial data collection included patients admitted in November 2021. We introduced a discharge template and education sessions for orthopaedic NCHDs regarding discharge summary completion. We then retrospectively collected data from discharge summaries completed after the intervention in March 2021 Results: We examined discharge summaries of 10 patients in each group. Admission and discharge details, and details of the patient, GP and author met the HIQA standards in all summaries and there was no significant change documented. There was an appropriate clinical narrative included for 8 patients preintervention and all patients after. There was a 70% improvement in documentation of patients' living circumstances and 90% for details of functional state. Medications on discharge were included for three patients initially and eight after. Specific details regarding medication changes were included for one patient initially and seven after. Details of future management improved in 5, 7 and 3 summaries regarding hospital actions, GP actions and community actions respectively. Conclusion: High-quality discharge summaries are essential for continuity of care and patient safety. The introduction of a discharge summary template and education of NCHDs significantly improved the quality of the discharge summaries in our unit.